リゾホスファチジン酸（LPA）がSLEモデルマウスの糸球体腎炎を改善させる - 永田, 亘; 小泉, 明穂; 中川, 慶一; 髙橋, さやか; 石塚, 俊晶 (日本薬理学会年会要旨集, 2022)
Objective: Lupus nephritis is a typical clinical manifestation of SLE. We previously reported that LPA treatment improves depressive-like behavior and microglial activation in MRL/lpr mice (an animal model of SLE). Thus, we examined the effects of LPA on renal function and glomerulonephritis in MRL/lpr mice. Method：18-week-old MRL+/+ mice (n=12) were treated with vehicle and 18-week-old MRL/lpr mice (n=24) were treated with vehicle or LPA (1 mg/kg) for 2 weeks. After the treatment, urine and blood samples were collected, and histological examinations were performed. Results and Discussion: The significant increases in daily urinary albumin levels in MRL/lpr mice were lost by LPA treatment. Creatinine in plasma was not significantly different between the three groups. The significant increases in plasma dsDNA antibody levels in MRL/lpr mice were lost by LPA treatment. The increases of CD68-positive cells in the glomerulus were found in MRL/lpr mice and the increases were suppressed by LPA treatment. The PAS-positive rates in MRL/lpr mice were significantly increased compared to MRL+/+ mice and the increases were significantly suppressed by LPA treatment. These results suggest that LPA treatment improves glomerulonephritis and proteinuria in MRL/lpr mice.